Flora tells a story: the Apocalypse of Paul and its contexts - Kaler, Michael (Studies in Christianity and Judaism, 2010)
In early Christianity, many people were inspired to write gospels, treatises, letters, and stories celebrating the new faith, but not all of these writings are found in the New Testament. One such story from an unknown author is the Coptic, gnostic Apocalypse of Paul, a tale of the apostle Paul's ascent to the heavens that was lost for millennia and rediscovered at Nag Hammadi in 1945. In Flora Tells a Story, Michael Kaler discusses the Apocalypse of Paul and how it was shaped by its literary environment. The book takes a behind the scenes look at early Christian literary production, analyz